A Study on Drug-Induced Tardive Dyskinesia: Orofacial Musculature Involvement and Patient's Awareness - Arunachalam M Anusa; Rooban Thavarajah; Dinesh Nayak; Elizabeth Joshua; Umadevi Krishnamohan Rao; Kannan Ranganathan (Wolters Kluwer Medknow Publications, 2018)
Aim and Objective: Schizophrenia is a psychiatric disorder that requires long-term treatment. Long-term antipsychotic treatment is often associated with the emergence of tardive dyskinesia (TD), the severity of which is measured by Abnormal Involuntary Movement Scale (AIMS). This study examined the relationship among TD, orofacial musculature activity, and patient's awareness of Abnormal Involuntary Movement (AIM). The knowledge would help dentists to deliver oral care for schizophrenics with TD. Materials and Methods: We identified 317 patients from a standard, data sharing initiative, of whom 38.3% exhibited AIM score of 2 to 15. The patient demographics, drug history, details of AIMS were subjected to descriptive and inferential statistical analysis using SPSS with P ≤ 0.05 as significance. Results: The mean of only orofacial features (n = 56) was 3.43 ± 2.68. Muscles of facial expression was involved in nine (7.9% of all TD), lip/perioral area in 27 (23.68%), jaw in 52 (45.61%), and tongue in 77 (67.54%). The patient's perception of AIM precipitated stress when involving jaw, tongue, limbs, and trunk was statistically significant (P ≤ 0.05). The multiple regression model statistically significantly predicted TD for factors considered. Conclusion: Around 1% of global population is being diagnosed with schizophrenia, carry an inherent risk of developing TD. They might have orodental care requirements, including prosthodontic and restorative services. Primary physicians and dentists need to be aware of TD and its mechanism for appropriate patient management.